The (non)politicisation of age discrimination in Finland and Sweden. Issue 9 (2nd September 2014) - Nygård, Mikael; Snellman, Fredrik
Abstract : Purpose: – The purpose of this paper is to examine the politicisation of age discrimination in relation to the enactment of anti-discrimination legislation in Finland and Sweden in the early-2000s. By showing how politicians constructed the meaning of age discrimination, it seeks to highlight the drivers of country variation in terms of the implementation of directives from the European Union (EU). Design/methodology/approach: – The paper uses a comparative design based on content analyses of parliamentary documents. Theoretically, it uses discursive institutionalism as a starting point but it also builds on previous research/theories on age discrimination. Findings: – The findings show that although age was seen as a ground for discrimination in both countries, there was surprisingly little debate about discrimination as societal problem. There was however considerable differences between the countries suggesting that age discrimination was a much more heated subject in Sweden. Research limitations/implications: – Although the analysis focuses on a small part of the policy-making process it highlights drivers (such as political culture) that may cause variation in the ways age discrimination is politicised, even within similar welfare state regimes. It also suggests that more research is needed to fully understand such drivers. Social implications: – The paper presents examples that can help analysts and the public to deconstruct institutionalised practices of age discrimination and thereby to understand how age discrimination practices may prevail in society. Originality/value: – By analysing the ways in which age discrimination was constructed as a problem within national policy-making frameworks, the paper presents valuable insights as to the sources of country variation in relation to the implementation of EU directives.